Durability in youth squad triathletes—influence of strenuous cycling on subsequent running performance, economy, and substrate utilization - Röhrs, G.; Keller, S.; Wahl, P. (International Journal of Sports Physiology and Performance, 2025)
Purpose: This study aimed to investigate oxygen/energy cost (OC/EC) of running and substrate utilization before and after strenuous cycling in well-trained junior triathletes and the relevance of changes in these variables for fatigued running performance.